Fine-scale conditions across mangrove microhabitats and larval ontogeny contributes to the thermal physiology of early stage brachyurans (Crustacea: Decapoda). Issue 1 (16th March 2021) - Vorsatz, L D; Pattrick, P; Porri, F
Abstract : Small-scale variations in microhabitat conditions influence the physiology of mangrove-associated crab larvae throughout their ontogeny. The zoeal stage is the most vulnerable as a bottleneck for successful keystone species' larval development in subtropical estuaries if climate anomalies persist in an already harsh intertidal environment. Abstract: Most marine ectotherms require the successful completion of a biphasic larval stage to recruit into adult populations. Recruitment of larvae into benthic habitats largely depends on biological interactions and favourable environmental conditions such as the inescapable diurnal thermal and tidal exposures. Hence, assessing how different taxa metabolically respond to variations in temperature is imperative to understand the community and ecosystem dynamics at both local and global scales. The present study aimed to investigate the effects of acute temperature variation on the physiology of stage-specific brachyuran larvae collected from different microhabitats at two mangrove forests in South Africa. Results indicate that the conditions within microhabitats, which larvae experience, likely influence their physiology, based on respirometry, to short-term acute temperature exposures. Furthermore, the larval thermal optimum shifted ontogenetically to become increasingly eurythermic as individuals developed from stage I zoea through to megalopa. Mangrove crab larvae in their early stages are hence increasingly vulnerable to acute temperature exposures, which could be particularly harmful to the persistence of populations if thermally stressful events increase in magnitude and frequency.